PENGARUH SHIFT KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI DIVISI LINEHAUL & SHUTTLE WAREHOUSE LAZADA CIMANGGIS - Arien Ramanta Wila (2021)
This research was using quantitative study aimed to see the influence of work shifts and work stress on employee performance. This study used employees of the Lazada Cimanggis Linehaul & Shuttle Warehouse Division as samples. The sample selection is done by lottery to get the number according to the Slovin formula, namely 80 people. Hypothesis testing this study used was the coefficient of determination (R2), t test and F test with a significance level of 5% (0.05). The results of the test obtained (1) there is a positive and significant influence between work shifts on employee performance, (2) there is a positive and significant influence between work stress on employee performance, (3) simultaneously there was an influence between work shift and work stress variables on employee performance.